The efficacy of radiofrequency ablation combined with transcatheter arterial chemoembolization for primary hepatocellular carcinoma in a cohort of 487 patients. - Hui Xie; Huaming Wang; Weimin An; Wei Ma; Ruping Qi; Bin Yang; Chunzi Liu; Yuanzhi Gao; Beibei Xu; Wenhong Wang (PLoS ONE)
Although diagnostic methods, surgical techniques, and perioperative care have undergone significant advancement over the past decades, the prognosis of primary hepatocellular carcinoma (HCC) remains discouraged because of the high postoperative recurrence rate and high cancer mortality. Radiofrequency ablation (RFA) combined with transcatheter arterial chemoembolization (TACE) is a recently developed means for the treatment of HCC. In this study, we analyzed the efficacy of RFA plus TACE in 487 cases of HCC in our institution. We observed that the 1-, 2-, 3-, 4- and 5-year rates of overall survival rates after RFA and TACE treatment were 97.5% (475/487), 89.4% (277/310), 84.2% (181/215), 80.4% (150/186) and 78.7% (141/177), respectively. We did not find that age or tumor location (the caudate group or non-caudate group) plays a role in this cohort. However, we have identified that tumor recurrent status, the number of tumors, albumin (ALB), prothrombin time (PT) and platelet count (PLT) were significantly associated with poor overall survival in HCC patients receiving RFA combined with TACE. Interestingly, tumor size did not significantly impact overall survival, indicating that RFA combined with TACE for HCC treatment has the same efficiency for different sizes of tumors. Our results provide evidence for the rationale for using combined RFA and TACE in the treatment of primary HCC.